Life cycle and justification of sustainable chemical control of oil palm fruit bunch moths on peat oil palm estates. - Su, Chong Ming (2020)
Indonesia and Malaysia are the world’s biggest oil palm producers that contribute 85% of the global palm oil supply, equivalent to 34% of world vegetable oils consumption in 2018. However, the oil palm industry is facing multifaceted challenges; among them are severe oil palm bunch moth, Tirathaba mundella Walker infestation that adversely affected the oil palm yield. In order to effectively and sustainably manage the pest, their life cycle and sensitivity to pesticide need to be understand. This study aims to formulate Tirathaba-specific artificial diet to allow laboratory rearing of the pest to study their life cycle. Second, to determine the economic destruction by T. mundella in the field through inter-correlate field census, fruit set counting and oil to bunch analysis. Third, to determine the optimum dosage of an anthranilic diamide insecticide, chlorantraniliprole as well as chromafenozide, an insect growth regulator against oil palm bunch moth, T. mundella Walker. Fourth, to identify the impact of insect growth regulators (IGRs) and other potential chemicals on the survival of oil palm pollinators, Elaeidobius kamerunicus. Last but not least, to evaluate the effectiveness of rotation mechanisms among chlorantraniliprole, insect growth regulators (IGRs), biological insecticide, Bacillus thuringiensis and other potential weevil friendly chemical insecticides with different mode of actions against T. mundella Walker in young mature oil palm plantation. The study found that the mean lifespan of T. mundella was 47 ± 4 days with 49% spent as larvae. The economic damage caused by T. mundella mainly in larvae stage and the result showed that the larvae count was positively correlated with the economic losses and number of malformed fruitlets. The overall oil extraction rate (OER) of moderate and severely infested fruit bunches was significantly reduced as compared to clean fruit bunches. Based on average crude palm oil market price and production per hectare, an Economic Injury Level (EIL) for T. mundella was estimated at 110 bunches with moderate infestation or 81 bunches of severe infestation. Such a low EIL would require an effective pest control approach that is not only cost effective and which will not harm the pollinating weevil. The results of this study suggested that both chromafenozide and pyridalyl were weevil friendly insecticides in addition to chlorantraniliprole, which has been established as weevil friendly insecticides in previous study. The optimum and most cost-effective pest control approach for one-year protection was found to be two rounds of 30.0 g active ingredient of chlorantraniliprole per ha rotated with two rounds of 25.0 g active ingredient of chromafenozide. The finding of this study would benefit future pest management practice in oil palm plantation established on peatland.